2019
DOI: 10.3390/molecules24050860
|View full text |Cite
|
Sign up to set email alerts
|

Drug-1,3,4-Thiadiazole Conjugates as Novel Mixed-Type Inhibitors of Acetylcholinesterase: Synthesis, Molecular Docking, Pharmacokinetics, and ADMET Evaluation

Abstract: A small library of new drug-1,3,4-thiazidazole hybrid compounds (3a–3i) was synthesized, characterized, and assessed for their acetyl cholinesterase enzyme (AChE) inhibitory and free radical scavenging activities. The newly synthesized derivatives showed promising activities against AChE, especially compound 3b (IC50 18.1 ± 0.9 nM), which was the most promising molecule in the series, and was substantially more active than the reference drug (neostigmine methyl sulfate; IC50 2186.5 ± 98.0 nM). Kinetic studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…[14] Nonetheless, in recent years, some 1,3,4-thiadiazole hybrid compounds presented for acetylcholinesterase enzyme inhibitory and showed promising activities against AChE. [21] α-Glycosidase enzymes are located on the brushy surface of the small intestine. They are responsible for breaking down complex carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Nonetheless, in recent years, some 1,3,4-thiadiazole hybrid compounds presented for acetylcholinesterase enzyme inhibitory and showed promising activities against AChE. [21] α-Glycosidase enzymes are located on the brushy surface of the small intestine. They are responsible for breaking down complex carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 4, zerumbone was predicted to possess good water solubility (−4.03 log mol/L), with appreciable absorption from the intestine (Caco-2 permeability > 0.90 × 10 −6 cm/s and human intestinal absorption >30%). The skin permeability value (−2.06 log Kp) of zerumbone, which defines the rate of a chemical passage through the stratum corneum, was comparable with that of the standard value (−2.5 log Kp), showing its potential as a lead structure and justifying its drug-likeliness behavior [17].…”
Section: In Silico Admet Predictions For the Bioavailability Of Zerumbonementioning
confidence: 66%
“…Previous studies reported interactions with the AChE amino acid residues with various antipsychotic drugs. Recent studies reported interactions with critical residues such as Leu288, Ser292, Thr237, Val238, Gln368, Pi-cation interaction with Arg295, Pialkyl and alkyl interactions with Pro289, Val299, Pro367, 234 of AChE [42,43] Donepezil and Pimozide ligands showed the lowest energy and the best favorable interactions. The Galanthamine (À7.3 kcal/mol) and Risvagtimine (À7.95 kcal/mol) showed higher binding energies than Donepezil (À8.5 kcal/mol) ligands [44].…”
Section: Molecular Dockingmentioning
confidence: 99%